Existence and uniqueness of a regular solution of the Cauchy-Dirichlet problem for the equation of turbulent filtration - Ivanov, Aleksandr V.; Jäger, Willi (Journal of mathematical sciences, 2000)
The existence and uniqueness of a regular solution of the Cauchy-Dirichlet problem for doubly nonlinear parabolic equations are proved, and inner and boundary weighted gradient estimates for these solutions are established. The equation of turbulent filtration is admissible for the results obtained. Bibliography: 19 titles.